Dependence of RF/analog and linearity parameters on ferroelectric layer thickness in ferroelectric tunnel junction dual material double gate (FTJ-DMDG) TFET. Issue 1 (2nd January 2023) - Saha, Rajesh; Panda, Deepak Kumar; Goswami, Rupam
Abstract: In this article, we have proposed a ferroelectric tunnel junction (FTJ) dual material double gate (DMDG) TFET using TCAD simulator, where a ferroelectric (FE) layer is incorporated at tunnel junction to increase the band to band tunnelling rate. TCAD simulation result reflects that the inclusion of FE layer leads to improved ON current with enhanced BTBT rate as the thickness of FE layer ( t FE ) is reduced from 4 to 2 nm. The RF/analog parameter like transconductance ( g m ), gain ( g m / g d ), cut off frequency ( f t ), transconductance generation factor (TGP), gain frequency product (GFP), and transconductance frequency product (TFP) are improved by noticeable amount with down scaling in t FE value. The linearity analysis like g m2, g m3, voltage intercept points (VIP2 and VIP3), power intercept point (IIP3 ), and 1-dB compression point are also highlighted in FTJ-DMDG-TFET by varying t FE . A noticeable improvement in linearity behaviour is perceived with increased value in t FE .